Comparative Evaluation of Dexamethasone and Dexmedetomidine as Adjuvants for Bupivacaine in Ultrasound-Guided Infraorbital Nerve Block for Cleft Lip Repair: A Prospective, Randomized, Double-Blind Study - El-Emam, El-Sayed M. (Anesth Essays Res, 2019)
PURPOSE: To compare dexamethasone (DA) to dexmedetomidine (DE) as adjuvants for bupivacaine during infraorbital nerve block (IONB) in a randomized clinical trial. PATIENTS AND METHODS: One hundred patients were randomized into two equal groups. By the guidance of ultrasound, the IONB was performed bilaterally in all patients, using 1 mL of the solution on each side. In DA group, 1 mL of 0.5% bupivacaine was added to 0.1 mg.kg−1 DA and diluted to 2 mL in DE group; 1 mL of 0.5% bupivacaine was added to 0.5 μg.kg(−1) DE and diluted to 2 mL. The primary outcome was time to first rescue analgesic. The secondary outcomes included face legs activity cry consolability (FLACC) score rating during the first 24 h, hemodynamic variables, the incidence of postoperative vomiting, sedation score, and parent satisfaction. RESULTS: During the first 24 h postoperatively, the DE group showed a significantly lower FLACC score and a longer time to first analgesic request compared to DA group. Sedation and parent satisfaction scores were significantly higher while heart rate and mean blood pressure were significantly lower in DE group compared to DA group. There were no differences in other secondary outcomes. CONCLUSION: The use of DE as an adjuvant to bupivacaine in IONB for cleft lip repair resulted in lower pain score and more prolonged duration of analgesia compared to DA.